The impact of electronic gadget uses with academic performance among secondary school students - Othman, Noratikah; Kelana, Muhammad Khairuz Suhaidi; Jamaludin, Thandar Soe Sumaiyah (Tridha Scholars Publishing Pvt. Ltd., 2020)
Introduction: Many school students who own electronic gadget spent most of their time on it. As a result, both of the aspect of academic achievement and health status is affected as they are too dependent on electronic gadget. Objective: The general objective of this study was to determine the association of electronic gadget use with academic performance and health status among selected secondary school students in Kuantan, Pahang. Materials and Methods: A descriptive, cross sectional study by using convenient sampling was conducted on sample size of 233 school students at three selected secondary schools involving SMK Pelindung, SMK Bukit Goh and SMK Teluk Chempedak. The instrument used was structured questionnaire to assess the total time spent on electronic gadget, students’ academic performance and students’ health status. The data was analysed by using SPSS version 20 in term of descriptive statistic and Pearson Chi-Square test to test the significant association. Result: There were 233 school students who involved in this study and majority of them (59.2%) were Malay. For gender, 53.2% were male and 46.8% were female. In total of 48.1% students were spending time more than 6 hours on electronic gadget and the remaining 51.9% students spending time less than 5.99 hours on electronic gadget. Based on the findings, the result showed that there were significant association between race, gender, parent income, level of dependency, academic performance and health status and the total time spent on electronic gadget but opposing, there were no significant association between years started using electronic gadget and total time spent on electronic gadget. Conclusion: Majority of students who spent more time on electronic gadget use has high level of dependency towards gadget, poor academic achievement and good health status. Thus, the healthcare providers should plan effective intervention such as introduce application on electronic gadget for academic purposes and health tracking to overcome these problems so that students can balance between their academic achievement and health status and increase wellness and health among school students.